The CGIAR at 40 : Institutional Evolution of the World’s Premier Agricultural Research Network - Ozgediz, Selcuk (World Bank, Washington, DC, 2016)
The Consultative Group on International Agricultural Research (CGIAR) has been one of the most successful research-for-development organizations over the past 40 years. The $11 billion invested by CGIAR donor members in research conducted by the international Centers under its umbrella has yielded many multiples of that sum in economic benefits to developing and emerging countries. Annual economic benefits of research on rice in Asia alone are equivalent to the total investment made by CGIAR donors over 4 decades, leaving aside benefits in other continents and from other research conducted by CGIAR institutions. The CGIAR‘s success is due in part to the way it was organized. The Group itself was an informal forum for dialogue among donor members about research priorities, investment options, and the continuing relevance and effectiveness of the institutions supported. The international centers constituted the core of the CGIAR. Each was (and still is) an autonomous international organization governed by an international board. The Group and the Centers were originally advised by the Technical Advisory Committee (TAC) of distinguished scientists from developing and developed countries, each appointed as an individual. The Group’s activities were facilitated by its Secretariat based at the World Bank in Washington, DC, and TAC’s activities by another secretariat based at the food and agriculture organization in Rome.